Ryanodane diterpenes from two Erythroxylum species - Barreiros, Marizeth L.; David, Juceni P.; David, Jorge M.; Lopes, Lucia M. Xavier; de Sa, Matheus S.; Costa, Jose F. O.; Almeida, Mara Z.; de Oueiroz, Luciano P.; Sant'Ana, Antonio E. G. (Elsevier B.V., 2007)
Ryanodane diterpenes, named 14-O-methyl-ryanodanol and ryanodanol, were isolated from ripe fruit of Erythroxylum passerinum. Compound 2 was also found in the leaves of this species, while 1 was obtained from the leaves of E. nummularia. Compound 1 showed insecticidal activity against Aedes aegypti larvae. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Erythroxylum passerimum; Erythroxylum numularia; Erythroxylaceae; ryanodane diterpenes; larvicidal activity